DAMPAK POLIGAMI TERHADAP HAK WARIS DAN STATUS ANAK: STUDI YURIDIS ATAS PRAKTIK POLIGAMI NONFORMAL - Nova Reana Wahida; Sidi Ahyar Wiraguna (Jurnal Riset Multidisiplin Edukasi, 2025)
This study examines the legal consequences of informal polygamy particularly unregistered or siri marriages on children’s civil status and inheritance rights under Indonesian law. Triggered by recurring cases in areas such as Kedung Banteng Village, Sidoarjo popularly dubbed the “polygamy village” this research addresses how children born from non-formal polygamous unions face systemic legal uncertainty regarding civil recognition, birth registration, and inheritance. Using a normative juridical approach with qualitative document analysis, the study reviews relevant legislation, court decisions (including Constitutional Court Decision No. 46/PUU-VIII/2010), scholarly literature, and factual cases reported by the Indonesian Association of Sharia Lawyers (APSI) and media sources. Findings reveal that children from informal polygamous marriages are often denied “legitimate child” status under Article 42 of Law No. 1/1974 on Marriage, hindering their access to birth certificates that include the father’s name and limiting their legal standing as heirs. Although the Constitutional Court affirms biological fathers’ civil responsibility toward children born out of wedlock, practical enforcement remains constrained by costly DNA testing, bureaucratic barriers, and lack of legal documentation. In Islamic inheritance law, recognition depends on whether the siri marriage fulfills religious requirements, yet this is insufficient without state validation. The study concludes that informal polygamy undermines the principle of the best interests of the child and violates Indonesia’s commitments under the Convention on the Rights of the Child. Legal harmonization, simplified recognition procedures for non-marital children, and public legal education are urgently needed to protect vulnerable children from long-term socio-legal marginalization.